2021
DOI: 10.1002/ece3.7654
|View full text |Cite
|
Sign up to set email alerts
|

Looking for the needle in a downsized haystack: Whole‐exome sequencing unravels genomic signals of climatic adaptation in Douglas‐fir (Pseudotsuga menziesii)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…The gene flow from warm and humid regions (EL and CN) to the cold and arid regions (NE and NW) was greater than the gene flow in the opposite direction, which was beneficial for increasing the genetic diversity of A. viridiflora in the cold and arid environments and enhancing its local adaptability. This result is in accord with studies on different populations of Silene ciliata ,Pseudotsuga menziesii and Eperua falcata (Brousseau, Fine, Dreyer, Vendramin, & Scotti, 2021;George et al, 2021;Morente-López et al, 2021). The G-phoCS results showed that A. viridifloradifferentiated into two lineages, NL and CW, 6.52 Mya.…”
Section: Demographic History and Gene Flow Among A Viridiflorasupporting
confidence: 91%
“…The gene flow from warm and humid regions (EL and CN) to the cold and arid regions (NE and NW) was greater than the gene flow in the opposite direction, which was beneficial for increasing the genetic diversity of A. viridiflora in the cold and arid environments and enhancing its local adaptability. This result is in accord with studies on different populations of Silene ciliata ,Pseudotsuga menziesii and Eperua falcata (Brousseau, Fine, Dreyer, Vendramin, & Scotti, 2021;George et al, 2021;Morente-López et al, 2021). The G-phoCS results showed that A. viridifloradifferentiated into two lineages, NL and CW, 6.52 Mya.…”
Section: Demographic History and Gene Flow Among A Viridiflorasupporting
confidence: 91%
“…3) is not in line with this knowledge. The subdivision into ecotypes that belong to both, the coastal and interior variety of Pseudotsuga menziesii on a small range, such as in British Columbia where we find populations of all ecotypes, indeed happens in a transition zone where we can expect a lot of substructure in populations [57,66]. This becomes evident when allowing for more clusters in SI, Fig.…”
Section: Differentiation Of Ecotypesmentioning
confidence: 85%
“…Our ecotypic classification is determined by the interplay of three climatic factors throughout the range of Douglas-fir that might have been responsible for part of the genotypic adaptations in its biogeographic history [66]. These predictors constrain ecotype identification by prior knowledge that is taken from the literature [13].…”
Section: Differentiation Of Ecotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the available 16‐Gbp assembly is rather fragmented (N50 scaffold = 340.7 kbp) and highly repetitive. Therefore, as a proxy to the prohibitive time and costs of genotyping by whole genome resequencing, a genotyping platform based on Douglas‐fir exome capture has been established (George et al ., 2021 ; Thistlethwaite et al ., 2017 ). Restriction site‐associated DNA sequencing (RADseq) could be another approach (Konar et al ., 2017 ).…”
Section: Introductionmentioning
confidence: 99%